Biological Significance of Kisspeptin–Kiss 1 Receptor Signaling in the Habenula of Teleost Species - Ogawa, Satoshi; Parhar, Ishwar S. (Frontiers in Endocrinology, 2018)
Kisspeptin is a neuropeptide, encoded by KISS1/Kiss1 gene, which primarily acts as the regulator of reproductive functions via its receptor, kisspeptin receptor (KissR) in vertebrates. In the brain, Kiss1 gene is mainly expressed in the hypothalamic region, but KissR gene is widely distributed throughout the brain, suggesting that kisspeptin-KissR system may be involved in not only reproductive but also non-reproductive functions. In non-mammalian vertebrates, there are two or more kisspeptin and KissR types. The zebrafish (Danio rerio) possess two kisspeptin (Kiss1 and Kiss2) and their respective receptors (KissR1 and KissR2). In the brain of zebrafish, while Kiss2 is expressed in the preoptic-hypothalamic area, Kiss1 is predominantly expressed in the habenula, an evolutionarily conserved epithalamic structure. Similarly, KissR1 is expressed only in the habenula, while KissR2 is widely distributed in the brain, suggesting that the two kisspeptin systems play specific roles in the brain. The habenular Kiss1 is involved in the modulation of the raphe nuclei and serotonin-related behaviours such as fear response in the zebrafish. This review summarizes the roles of multiple kisspeptin-KissR systems in reproductive and non-reproductive functions and neuronal mechanism, and debates the biological and evolutional significance of habenular kisspeptin-KissR systems in teleost species.